Memahami Dinamika Perkembangan Remaja: Fisik, Emosi, dan Kognitif dalam Layanan Konseling Bimbingan Konseling dalam Menyikapi Perubahan Fisik dan Emosi Remaja - latif, nur wahidah; Nasrudin, Muhammad Farhan; Prasetyo, Ahmad Agung; Nastain, Muhammad; Mukaromah, Annisa; Hamam, naufal Muhammad; Fathoni, Tamrin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Abstract Adolescence is a very crucial period because During this period children experience many psychological and physical changes his physique. The occurrence of mental changes causes confusion among teenagers, they experience full emotional turmoil and mental pressure resulting in deviating from rules and norms social issues that prevail among society. Apart from that, adolescence is also marked by a search for identity, independence, and exploration of social and emotional roles. Teenagers tend to develop their own outlook on life, values and preferences, often influenced by family, peers and the surrounding environment. In the process of development of psychological maturity and biologically, teenagers often face tension, confusion, and worries. Teenagers are fond of experimenting with unstable emotions so easily influenced. Keywords: development, teenager, physical, emotion, cognitive, counselling guidance